Youth Perceptions on State Institutional Capacity for Their Empowerment in Yobe State, Northern Nigeria - Alhaji Ahmadu Ibrahim; Julius Kiiza; Peter Atekyereza (Richtmann Publishing, 2023)
There has been growing concern over the state’s inability to effectively respond to Nigeria's persistent rise in poverty and unemployment. This concern is more among the youth, who feel they have not been empowered enough. This article examines the nature of Yobe State's institutional capacity, its impact on youth empowerment, and its implications on employment and poverty reduction. It is based on a study that adopted a mixed-methods sequential approach combining quantitative and qualitative data collection methods. In the first phase, 393 randomly selected respondents were interviewed using a semi-structured questionnaire. In the second phase, data were collected on key informants and youth participants' opinions, views, and experiences using key informant interviews, in-depth interviews, and focus group discussions. The findings reveal that most youth are not confident of the state's institutional capacity to implement youth empowerment programs effectively. Most of the youth participants and key informants are not satisfied with the expertise of the state empowerment institutions to manage the implementation of the empowerment programs in the state. The factor analysis shows a 64.4% variation in institutional capacity to implement youth empowerment programs, meaning improvement in state capacity and state competence in implementing youth empowerment programs may lead to 64.4% towards youth empowerment in the state. Therefore, the study recommends that Yobe State Government strengthens its institutions responsible for designing and implementing empowerment programs through adequate funding and recruitment of adequate, relevant, and professional staff to ensure policy sustainability. Received: 23 March 2023 / Accepted: 29 June 2023 / Published: 5 July 2023